BETULA TURKESTANIKA ROTH. COMPARATIVE STUDY OF PLANT BARK EXTRACT SUBSTANCES - Boboyorova Sh.M; Berdiyev E.T; Khaitov F.J; Yuldashev Kh.A (TADQIQOTLAR.UZ, 2023)
In this article Betula Turkestanika Roth. which grows on the territory of our republic the results of a comparative study of extractive substances of white birch bark using different solvents are presented.